Ekonomiczne perspektywy rozwoju obszaru działalności Unii Izb Łaby/Odry - Michael Bräuninger; Silvia Stiller; Mark Teuber; Jan Wedemeier (Hamburgisches WeltWirtschaftsInstitut (HWWI), 2012)
Unia Izb Łaby/Odry to związek 15 niemieckich, 6 polskich i 9 czeskich izb przemysłowo-handlowych, który za cel stawia sobie wspólne reprezentowanie interesów przedsiębiorstw z tego obszaru na szczeblu krajowym i europejskim. W roku 2010 na obszarach działalności poszczególnych Izb mieszkało 37 mln osób, co odpowiada 7,5 % ludności Unii Europejskiej (EU). Produkt krajowy brutto (PKB) Regionu wyniósł w 2008 roku 718 mld EUR, co stanowi 6 % PKB Unii Europejskiej. – – The Elbe/Oder Chamber Union (KEO) is a consortium of German, Polish and Czech chambers of industry and commerce, which has set itself the goal of jointly representing the interests of companies in the region at a national and European level. In 2010, 37.6 million people lived in the represented region, representing a market share of 7.5% of the EU population. The gross domestic product of the KEO region in 2008 was 716.6 billion Euros, equal to 5.7% of the total EU GDP. Despite the overall strength of the region, there are pronounced differences within each member state which can be addressed and equalized through joint cooperation. Also, as both foreign and interregional trade is increasing in the KEO area, it is important that member states focus on their core competencies and, through doing so, work together towards an economically viable future. Many policy areas have been identified in order to strengthen the competitiveness of these regions, among them the development of research capabilities, the reduction of transaction costs for cross-border activities and the qualitative and quantitative improvement of the transport infrastructure are particularly relevant.
Keywords: 330; Wirtschaftslage; Regionale Entwicklung; Handelskammer; Elbe; Oder